2022
DOI: 10.3390/antiox11112166
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Radiosensitizing Effect of Carnosic Acid on B16F10 Metastatic Melanoma Cells: A New Treatment Strategy

Abstract: Carnosic acid (CA) is a phenolic diterpene characterized by its high antioxidant activity; it is used in industrial, cosmetic, and nutritional applications. We evaluated the radioprotective capacity of CA on cells directly exposed to X-rays and non-irradiated cells that received signals from X-ray treated cells (radiation induced bystander effect, RIBE). The genoprotective capacity was studied by in vivo and in vitro micronucleus assays. Radioprotective capacity was evaluated by clonogenic cell survival, MTT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Based on these results, it is suggested that the inhibition of EMT might be a key factor contributing to the reduced cell migration in B16F10 cells treated with CrA [376]. In a recent study by Alcaraz et al (2022), CrA was identified as a potent radiosensitizing agent [377]. The research demonstrated that when B16F10 melanoma cells were exposed to X-ray irradiation, CrA significantly reduced their cell survival, indicating its potential to enhance the effectiveness of radiotherapy in treating melanoma.…”
Section: Other Phenolic Compoundsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on these results, it is suggested that the inhibition of EMT might be a key factor contributing to the reduced cell migration in B16F10 cells treated with CrA [376]. In a recent study by Alcaraz et al (2022), CrA was identified as a potent radiosensitizing agent [377]. The research demonstrated that when B16F10 melanoma cells were exposed to X-ray irradiation, CrA significantly reduced their cell survival, indicating its potential to enhance the effectiveness of radiotherapy in treating melanoma.…”
Section: Other Phenolic Compoundsmentioning
confidence: 91%
“…In addition, RA also enhanced the sensitivity of melanoma cells to cisplatin [241]. Additionally, the radiosensitizing effect of RA in melanoma B16F10 cells was documented and this effect can be associated with decreased GSH-dependent protection against oxidative stress [242,243]. Moreover, oral administration of RA completely prevented DMBA-induced carcinogenesis in Swiss albino mice.…”
Section: Phenolic Acidsmentioning
confidence: 96%